Clustering of chronic hepatitis B screening intentions in social networks of Moroccan immigrants in the Netherlands - Hamdiui, Nora; Buskens, Vincent; Van Steenbergen, Jim E.; Kretzschmar, Mirjam E.E.; Rocha, Luis E.C.; Thorson, Anna E.; Timen, Aura; Wong, Albert; Van Den Muijsenbergh, Maria; Stein, Mart L. (BioMed Central Ltd., 2020)
Background: Early detection, identification, and treatment of chronic hepatitis B through screening is vital for those at increased risk, e.g. born in hepatitis B endemic countries. In the Netherlands, Moroccan immigrants show low participation rates in health-related screening programmes. Since social networks influence health behaviour, we investigated whether similar screening intentions for chronic hepatitis B cluster within social networks of Moroccan immigrants. Methods: We used respondent-driven sampling (RDS) where each participant ("recruiter") was asked to complete a questionnaire and to recruit three Moroccans ("recruitees") from their social network. Logistic regression analyses were used to analyse whether the recruiters' intention to request a screening test was similar to the intention of their recruitees. Results: We sampled 354 recruiter-recruitee pairs: For 154 pairs both participants had a positive screening intention, for 68 pairs both had a negative screening intention, and the remaining 132 pairs had a discordant intention to request a screening test. A tie between a recruiter and recruitee was associated with having the same screening intention, after correction for sociodemographic variables (OR 1.70 [1.15-2.51]). Conclusions: The findings of our pilot study show clustering of screening intention among individuals in the same network. This provides opportunities for social network interventions to encourage participation in hepatitis B screening initiatives.
Keywords: Adult; Cluster Analysis; Emigrants and Immigrants/psychology; Female; Hepatitis B, Chronic/diagnosis; Humans; Intention; Male; Mass Screening/psychology; Middle Aged; Morocco/ethnology; Netherlands; Patient Acceptance of Health Care/ethnology; Pilot Projects; Social Networking; Surveys and Questionnaires; Journal Article